2015
DOI: 10.3892/ol.2015.3861
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of psoralidin in enhancing apoptosis of colon cancer cells via nuclear factor-κB and B-cell lymphoma-2/B-cell lymphoma-2-associated X protein signaling pathways

Abstract: Abstract. Worldwide, colon cancer is the third most common cancer in terms of incidence, following lung and breast cancer. Resistance to psoralidin frequently occurs following its use as an anticancer treatment. However, the mechanisms underlying the effects of psoralidin on colon cancer, remain to be elucidated. Hence, the present study investigated the anticancer effects and potential mechanism of action of psoralidin on SW480 human colon cancer cells. In the present study, an MTT assay was performed to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Therefore, we aimed to investigate whether PL could reverse excessive caffeine-caused injury in vitro and in vivo and, if so, to elucidate the underlying mechanisms. Documented studies have demonstrated that PL regulates several extracellular signaling pathways, which include the protein kinase B/glycogen synthase kinase 3β/β-catenin signaling pathway, the nuclear factor-kappa B (NF-κB) and phosphatidylinositol 3 kinase (PI3K)/Akt signaling pathway, and the NF-κB and B-cell lymphoma-2 (Bcl-2)/ Bcl-2 associated X protein (Bax) signaling pathway (16,29,30). Previous studies have demonstrated that PL can inhibit the formation of adipocytes by modulating the classical and membrane ER pathways (16).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we aimed to investigate whether PL could reverse excessive caffeine-caused injury in vitro and in vivo and, if so, to elucidate the underlying mechanisms. Documented studies have demonstrated that PL regulates several extracellular signaling pathways, which include the protein kinase B/glycogen synthase kinase 3β/β-catenin signaling pathway, the nuclear factor-kappa B (NF-κB) and phosphatidylinositol 3 kinase (PI3K)/Akt signaling pathway, and the NF-κB and B-cell lymphoma-2 (Bcl-2)/ Bcl-2 associated X protein (Bax) signaling pathway (16,29,30). Previous studies have demonstrated that PL can inhibit the formation of adipocytes by modulating the classical and membrane ER pathways (16).…”
Section: Discussionmentioning
confidence: 99%
“…Psoralidin has also shown promising results in combating breast, colon, prostate and liver cancer by activating oxidative stress, promoting DNA damage via NADPH oxidase 4 (NOX4)-mediated ROS production, decreasing the cell viability and inducing apoptosis (Ren et al 2016 ) (Jin et al 2016 ) (Bin et al 2019 ) (Szliszka et al 2011 ). Despite its broad activity, human clinical trials with psoralidin are scarce with only the effect of this molecule on dermatological conditions being previously investigated (Gopal et al 2001 ).…”
Section: Plant Secondary Metabolites As Alpha-glucosidase Inhibitorsmentioning
confidence: 99%
“…PSO promotes cellular apoptosis and inhibits the cancer cells proliferation in prostate cancer (Szliszka et al, 2011;Das et al, 2014); breast cancer (Dwarampudi et al, 2012); liver cancer (Luo et al, 2013); colon cancer (Jin et al, 2016a); esophagal carcinoma (Jin et al, 2016b), or modulate the autophagy in the lung (Hao et al, 2014;Xin et al, 2019).…”
Section: In Vitro Studiesmentioning
confidence: 99%